Peer-to-Peer Learning Process (PPLP) Framework to Enhance Problem Solving Skills - Abirami, A. M.; Karthikeyan, P.; Thangavel, M. (Journal of Engineering Education Transformations, 2025)
Present generation of students give less attention in class. This is a serious issue among college or university-level students. The faculty members have to use active learning strategies to have better student engagement in their classes. The faculty has to carefully design these pedagogical practices in such a way that more than one student gets involved in the activities in groups instead of in solo performances. This article details an innovative teaching-learning practice namely Peer-to-Peer Learning Process (PPLP) framework for improving the problem-solving skills of students. The experimental results show that the use of the PPLP framework in the class would enhance the academic performance of students.